ANTIOXIDANT EFFECT OF MOUTHWASH CONTAINING ZINC, ALOE VERA, AND STABILIZED CHLORINE DIOXIDE FOR ORAL MANIFESTATION OF ACUTE MYELOBLASTIC LEUKEMIA (AML) - PERMATASANTI, AYU; FITRIASAR, NURI; SARI, NUR MELANI; WAHYUNI, INDAH SUASANI (International Journal of Applied Pharmaceutics, 2023)
Objective: This paper aims to report a study regarding the successful treatment using zinc, Aloe vera, and stabilized chlorine dioxide as an antioxidant mouthwash in a patient with AML. Methods: A series of clinical examinations, including subjective and objective examinations, were done to establish the diagnosis. Results: A 9 y old boy, who was already diagnosed with AML, referred to the oral medicine division because of the hemorrhagic crust of his lips. The extra-oral examination showed severe hemorrhagic crust and erosions on the upper and lower lips. The intra-oral examination could not be evaluated in detail, but the active bleeding was seen. A hematology investigation showed pancytopenia. Patients received packed red cell (PRC) and thrombocyte concentrate (TC) blood transfusions, as well as an antioxidant mouthwash containing zinc, Aloe vera, and stabilized chlorine dioxide, for compressing the lips every 1-2 h with a duration of 30 min. Significant improvement in lip lesions was gained in a short time after blood transfusions and regular use of the mouthwash compresses. Conclusion: In this study, the mouthwash containing zinc, Aloe vera, and stabilized chlorine dioxide that can accelerate the healing process in our AML patient was estimated due to its antioxidant effects.